Effect of load inductance on inter-turn fault in single phase PMSG using Winding Function Theory - Parashar S.; Srivastava R.K. (My University, 2025)
The paper deals with effect of the load inductance on inter-turn fault for single phase permanent magnet synchronous generator. Fault often goes unnoticed in generators like single phase PMSG and therefore, study of fault behavior for different loads at terminal becomes necessary. For this purpose a mathematical model has been developed for an unhealthy generator using the Winding Function Theory. The effect of fault severity on the terminal voltage and fault current has been analyzed for load inductance of 2H and 6 H. Moreover, the effect of fault upon the counter torque applied on the generator has been studied by mathematical equations. Inter-turn fault generates large circulating currents which exert undesirable counter torque on the generator. Appropriate explanations have been provided for the obtained results. The results obtained by mathematical model have been verified by the simulation and experimental results. © 2015 IEEE.